Laparoscopic versus open radical hysterectomy in women with early stage cervical cancer: A systematic review and meta-analysis - Tanitra Tantitamit (Taiwanese Journal of Obstetrics & Gynecology, 2020)
This review aimed to evaluate the short term and long-term outcomes of laparoscopic radical hysterectomy (LRH) versus abdominal radical hysterectomy (ARH) for early-stage cervical cancer. A search of PubMed, Medline and Scopus databased from 2000 to 2018 was conducted. Thirty studies were retrieved including 22 retrospective cohort studies and 8 prospective cohort studies. LRH was comparable with ARH in 5-year overall survival (RR = 1.0. 95%CI 0.98–1.03; p = 0.33) and 5-year disease-free survival (RR = 1.02 95%CI 0.97–1.06; p = 0.98). The majority of included studies reported the negative cancer factors which drive adjuvant therapy were similar between two approaches. LRH was associated with lower blood loss and blood transfusion, less postoperative complication, shorter hospital stays and similar intraoperative complication rate compared to ARH. Our data suggested LRH for early-stage cervical cancer was as safe and effective in terms of long-term outcomes, but with lower surgical morbidities.